Injustice in Urban Sustainability Ten Core Drivers - Kotsila, Panagiota (Routledge Equity, Justice and the Sustainable City series, 2023)
This book uses a unique typology of ten core drivers of injustice to explore and question common assumptions around what urban sustainability means, how it can be implemented, and how it is manifested in or driven by urban interventions that hinge on claims of sustainability. Aligned with critical environmental justice studies, the book highlights the contradictions of urban sustainability in relation to justice. It argues that urban neighbourhoods cannot be greener, more sustainable and liveable unless their communities are strengthened by the protection of the right to housing, public space, infrastructure and healthy amenities. Linked to the individual drivers, ten short empirical case studies from across Europe and North America provide a systematic analysis of research, policy and practice conducted under urban sustainability agendas in cities such as Barcelona, Glasgow, Athens, Boston and Montréal, and show how social and environmental justice is, or is not, being taken into account. By doing so, the book uncovers the risks of continuing urban sustainability agendas while ignoring, and therefore perpetuating, systemic drivers of inequity and injustice operating within and outside of the city. Accessibly written for students in urban studies, critical geography and planning, this is a useful and analytical synthesis of issues relating to urban sustainability, environmental and social justice.